Hubungan Motivasi dan Ketangguhan Mental Terhadap Prestasi AtletTaekwondo di Kota Bandung - Tiara Khumairah Juliany Rukman; Herman Subarjah; Septian Williyanto; Mustika Fitri; Sandey Tantra Paramitha; Ahmad Hamidi (Journal of Sport Coaching and Physical Education, 2024)
Athletes' success in achieving optimal performance is not solely dependent on physical and technical abilities but is also influenced by psychological factors such as motivation and mental toughness. This study aims to examine the relationship between motivation and mental toughness in relation to the performance of Taekwondo athletes in Bandung City. Using a correlational quantitative method with 36 respondents, the study employed the Sport Motivation Scale (SMS-28) and the Sport Mental Toughness Questionnaire (SMTQ). The analysis revealed that motivation has a significant positive relationship with athletic performance, with higher motivation increasing the likelihood of achieving optimal results. Mental toughness also contributes significantly to performance, although its impact is somewhat weaker than motivation. Motivation provides the primary drive for athletes to continue training, face challenges, and maintain consistency in competition. Mental toughness enables athletes to stay focused under pressure, manage stress, and recover from setbacks, thereby supporting optimal performance. The results indicate that a combination of strong motivation and high mental toughness is a key factor in athletes' success. Support from coaches, families, and mental strength programs is crucial for optimizing both of these factors. This study offers valuable insights into the psychological aspects affecting athlete performance and suggests the development of interventions based on motivation and mental toughness to enhance the performance of Taekwondo athletes